Porous Silicon Formation by Electrochemical Etching - Оrest Kuntyi; Galyna Zozulya; Mariana Shepida (Advances in Materials Science and Engineering)
Porous silicon (PSi) is used as an effective material in biomedicine, sensors, solar cells, electrochemical energy, microelectronics, and nanotechnology. Considering the dependence of PSi functional properties on pore geometry and porous layer architecture, it is important to develop methods for controlled pore formation. After all, in the “procession” the method of obtaining PSi ⟶ pore geometry and architecture of PSi ⟶ functional properties of PSi, the decisive role belongs to the first participant. Among the most used methods, electrochemical etching is the most suitable for the controllability of the processes of nucleation and growth of pores since it can be controlled using the value of the current density, and the results are easily reproduced. This work analyses the literature on two types of electrochemical formation of PSi by anodic etching of (1) silicon surface and (2) silicon surface, modified with metal nanostructures. A modern explanation of the process of anodic dissolution of silicon with forming a porous surface in solutions containing HF is presented. The influence of such main factors on the process of anodic formation of PSi and its morphology is analyzed: the composition of the electrolyte and the role of each component in it; anode current density and methods of its supply (stationary, pulsed); duration; exposure to lighting; and temperature. Considerable attention is paid to the illustration of the role of alcohols and organic aprotic solvents on the formation of pore geometry. The influence of MNPs and metallic nanostructures on the process of localized metal-activated anodic etching of a semiconductor is analyzed.